A Comparative Study of Three Low-molecular Weight Heparins (LMWH) and Unfractionated Heparin (UH) in Healthy Volunteers - Eriksson, Bengt I; Söderberg, Karin; Widlund, Lars; Wandeli, Baback; Tengborn, Lilian; Risberg, Bo (Thrombosis and Haemostasis, 1995)
The levels of anti-IIa and anti-Xa activity, as reported in laboratory and clinical studies on low molecular weight heparin (LMWH) preparations, show a high degree of variability. This variation has been proposed as correlated to the variation in incidence of postoperative deep vein thrombosis (DVT) (8-30%) in different LMWH studies on comparable populations undergoing elective hip surgery. The aim of this study was to compare the ex vivo potency of Clexane® (enoxaparin), Fragmin® (dalteparin) and Logiparin® (tinzaparin), applying the concept of bioequivalence, although unknown which activity/activities are best correlated to efficacy. Unfractionated heparin (UH) was included in the study as a reference drug.The drugs were studied with a cross-over technique in 12 healthy subjects and given subcutaneously in the doses recommended for orthopedic surgery. Blood samples were drawn each hour up to 10 h and at 12 h after administration. Anti-Xa and anti-IIa activities were measured using chromogenic substrate methodsThe anti-Xa peak activity (Cmax) and the area under the curve (AUC) were highest for Clexane® and Fragmin® and lower for Logiparin® and UH. Clexane® and Fragmin® were considered bioequivalent in anti-Xa activity. Regarding anti-IIa activity, no bioequivalence was found between the products. Fragmin® was clearly different, with Cmax and AUC approximately twice as high as the other drugs. Whether the demonstrated differences in anti-Xa and anti-II activities are of any clinical significance remains unclear and can only be established by comparative clinical studies.